An Analysis of Negative Politeness Strategy Used By Anna in Anna and The King Movie (A Sociolinguistics Approach) - Ari Muhammad Syifa Syifa; Binti Qaniah; Endang Suciati (Journal of Research in Foreign Language Teaching (JRFLT), 2021)
This study is entitled An Analysis of Negative Politeness Strategy Used by Anna in Anna and the King Movie (A Sociolinguistics Approach). This study describes negative politeness strategies in a sociolinguistics approach based on negative politeness strategy theory proposed by Brown and Levinson and adapted on sociolinguistics theory by Holmes. The purpose of this study was to investigate negative politeness strategies in a sociolinguistics approach, to explain negative politeness strategies in a sociolinguistics approach, and to explain the reasons of the dominant strategy was applied by Anna in Anna and the King movie. The study used the descriptive qualitative method (Miles, Huberman, and Saldaña., 1994), which explained the data narratively. The data of this study were Anna's utterances which contain negative politeness strategy in Anna and the King movie. This study found 9 out of 10 strategies used by Anna on her utterances. The strategies are as follows; 1) Be conventionally indirect, 2) hedging, 3) Be pessimistic, 3) Minimize the imposition (MTI), 5) Give deference, 6) Apologize, 7) Impersonate S and H, 8) State the FTA as a general rule, 9) Nominalize. Each strategy contained a social dimension of sociolinguistics namely; Social Distance, Social Status, Formality Form of Language, and the Purpose of the interaction. In addition, the hedging strategy was the dominant strategy used by Anna because of the flexibility, and the social dimension of sociolinguistics in Anna’s utterances in Anna and the King movie.